B0 shimming of the human heart at 7T. Issue 1 (23rd July 2020) - Hock, Michael; Terekhov, Maxim; Stefanescu, Maria Roxana; Lohr, David; Herz, Stefan; Reiter, Theresa; Ankenbrand, Markus; Kosmala, Aleksander; Gassenmaier, Tobias; Juchem, Christoph; Schreiber, Laura Maria
Abstract : Purpose: Inhomogeneities of the static magnetic B0 field are a major limiting factor in cardiac MRI at ultrahigh field (≥ 7T), as they result in signal loss and image distortions. Different magnetic susceptibilities of the myocardium and surrounding tissue in combination with cardiac motion lead to strong spatio‐temporal B0 ‐field inhomogeneities, and their homogenization (B0 shimming) is a prerequisite. Limitations of state‐of‐the‐art shimming are described, regional B0 variations are measured, and a methodology for spherical harmonics shimming of the B0 field within the human myocardium is proposed. Methods: The spatial B0 ‐field distribution in the heart was analyzed as well as temporal B0 ‐field variations in the myocardium over the cardiac cycle. Different shim region‐of‐interest selections were compared, and hardware limitations of spherical harmonics B0 shimming were evaluated by calibration‐based B0 ‐field modeling. The role of third‐order spherical harmonics terms was analyzed as well as potential benefits from cardiac phase–specific shimming. Results: The strongest B0 ‐field inhomogeneities were observed in localized spots within the left‐ventricular and right‐ventricular myocardium and varied between systolic and diastolic cardiac phases. An anatomy‐driven shim region‐of‐interest selection allowed for improved B0 ‐field homogeneity compared with a standard shim region‐of‐interest cuboid. Third‐order spherical harmonics terms were demonstrated to be beneficial for shimming of these myocardial B0 ‐field inhomogeneities. Initial results from the in vivo implementation of a potential shim strategy were obtained. Simulated cardiac phase–specific shimming was performed, and a shim term‐by‐term analysis revealed periodic variations of required currents. Conclusion: Challenges in state‐of‐the‐art B0 shimming of the human heart at 7 T were described. Cardiac phase–specific shimming strategies were found to be superior to vendor‐supplied shimming.